The Analysis of Frerechtslehre Flow (The Judge's Creativity in Finding Law) Eungen Ehrlich in Justice and Human Rights Protection - RONU, Janang Mula Andri; MARSIANSYAH; PRATAMA, Ananda Takdir; SUPARNA, Brilian Albar Dwi; ASIHAY, Yayang; DODY; JOVI; KRISTHY, Mutia Evi (Journal of Political And Legal Sovereignty, 2023)
Purpose:Freirechtslehre is an approach that recognizes that law consists of written rules and is based on community practice and experience. In this analysis, first of all, Eungen Ehrlich's background and contribution to the development of the Freirechtslehre school are explained. Ehrlich emphasizes the importance of understanding law holistically by involving social, cultural, and economic factors in making legal decisions.Methodology:The research method that can be used in this analysis is descriptive. This method aims to describe and analyze the flows of Freirechtslehre developed by Eungen Ehrlich and its implications for judges' creativity in finding laws in the context of justice and human rights protection.Findings:This study concludes that the Freirechtslehre school significantly contributes to our understanding of judges' creativity in finding law and the importance of justice and the protection of human rights.Implication:In carrying out their duties, judges need to develop creativity in understanding and applying the law and consider the social context and values of justice to achieve justice and adequate protection of human rights